Tibial Hydatid Disease Mimicking Osteosarcoma: A Case Report and Diagnostic Challenges - Mahmoudi, Asma; Belkacem, Oussama; Mhiri, Amir; Krifa, Marwa; Mtaoumi, Mourad; Mestiri, Sara; Hmissa, Sihem (Biomedicine & Healthcare Research, 2026)
Background: Hydatid disease is a parasitic infection caused by Echinococcus granulosus, most commonly involving the liver and lungs. Osseous involvement is rare and can mimic malignant tumors, leading to diagnostic challenges and potential delays in treatment. Case Presentation: We report the case of a 25-year-old woman presenting with a rapidly progressive, painful swelling of the anterior right leg. Imaging studies suggested an aggressive bone lesion consistent with osteosarcoma. However, ultrasound findings raised suspicion of osseous hydatidosis, which was later confirmed by aspiration cytology and histopathological analysis. The patient underwent surgical excision of the cyst with intraoperative sterilization, followed by histopathological confirmation of tibial hydatid disease. Discussion: Osseous hydatidosis remains a diagnostic challenge due to its nonspecific clinical and radiological features. The main differential diagnoses include osteosarcoma, osteomyelitis, and benign cystic lesions. Imaging modalities such as ultrasound, computed tomography and magnetic resonance imaging play a crucial role, but definitive diagnosis relies on histopathological examination. Treatment involves surgical excision combined with antiparasitic therapy to prevent recurrence. Conclusion: This case highlights the importance of considering hydatid disease in the differential diagnosis of lytic bone lesions, especially in endemic regions. Early recognition and appropriate management are essential to prevent complications and improve patient outcomes.